ڕۆڵ و پێگەی پیاوانی ئایینی لە بونیاتنانی دەوڵەتی ساسانی (٢٢٦ – ٢٩١ز) - ئەنوەر, پ.د. کەیوان ئازاد; حسێن, شهرام شیروان (Sulaimani Journal for Humanities, 2023)
The Sassanian community was divided into several classes, and religious men were one of them. There were many religions and religious beliefs in the community. ter establishing Sassanian empire by )Ardasher Son Of Babak(, he declared Zoroastrianism as the official religion of his state, religious men, whose roles and positions were strong and widespread, had an active role in the lives of individuals of the Sassanian community, and because of the closeness and importance of their position, the King consulted them on the issues of the empire, meanwhile they played a major role in the political sphere. They were the source of directing events within the Sassanian community. Often their power was more expanded to the kings. They could make kings and take them out of their throne on their own free will. This effect remained strong and wide throughout the empire's history, and their participation and role were not the same, just as they played a role in building power, and they also played a role in the collapse of power.